1998
DOI: 10.1042/bj3300581
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic properties of class A β-lactamases: efficiency and diversity

Abstract: beta-Lactamases are the main cause of bacterial resistance to penicillins, cephalosporins and related beta-lactam compounds. These enzymes inactivate the antibiotics by hydrolysing the amide bond of the beta-lactam ring. Class A beta-lactamases are the most widespread enzymes and are responsible for numerous failures in the treatment of infectious diseases. The introduction of new beta-lactam compounds, which are meant to be 'beta-lactamase-stable' or beta-lactamase inhibitors, is thus continuously challenged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
306
1
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(321 citation statements)
references
References 200 publications
7
306
1
7
Order By: Relevance
“…Molecular comparisons of the various class A enzymes were facilitated by the use of a standard numbering scheme, as indicated by the label "ABL" (for class A ␤-lactamase) (96). Several years later, Matagne et al confirmed these findings and updated the list of residues that are involved in the catalytic mechanism and/or in substrate binding (12). Such characteristic residues have also recently been identified in 67 putative ␤-lactamases (97).…”
Section: Primary Structure/sequence Analysissupporting
confidence: 50%
See 2 more Smart Citations
“…Molecular comparisons of the various class A enzymes were facilitated by the use of a standard numbering scheme, as indicated by the label "ABL" (for class A ␤-lactamase) (96). Several years later, Matagne et al confirmed these findings and updated the list of residues that are involved in the catalytic mechanism and/or in substrate binding (12). Such characteristic residues have also recently been identified in 67 putative ␤-lactamases (97).…”
Section: Primary Structure/sequence Analysissupporting
confidence: 50%
“…This second motif was also observed in TEM-1 produced by Gramnegative bacteria (96). Given the narrow spectrum of activity of such enzymes, no amino acid substitution for expanded-spectrum resistance or resistance to inhibitors could be identified (12,114,115). Finally, the deletion of two residues between Ser218 and Ile221, in enzymes produced by several mycobacteria such as M. fortuitum, was found to be unique to the class A ␤-lactamases of Gram-positive bacteria (Fig.…”
Section: Enzymes Produced By Gram-positive Bacteriamentioning
confidence: 89%
See 1 more Smart Citation
“…The class A ␤-lactamase TEM-1 presents a significant clinical antibiotic resistance problem because of mutations that alter the substrate specificity to allow hydrolysis of extended spectrum cephalosporins or provide for inhibitor resistance (3)(4)(5)(6)(7)(8). The serine ␤-lactamase mechanism is similar to that of serine proteases (44), in that a proton is abstracted from the side chain oxygen of serine that acts a nucleophile and attacks the amide bond of the ␤-lactam ring (14,15,(17)(18)(19)(20)(21)24).…”
Section: Discussionmentioning
confidence: 99%
“…cleaved, inactive ␤-lactam) (38). The formation of the enzymatically inactive (covalent) acyl-enzyme complex (E-I) is known as the acylation step.…”
Section: Comparison Of Tp47 Withmentioning
confidence: 99%